The molecular mechanism of γ-aminobutyric acid against AD: the role of CEBPα/circAPLP2/miR-671-5p in regulating CNTN1/2 expression. Issue 4 (3rd February 2023) - Meng, Na; Pan, Pengyu; Hu, Shuang; Miao, Chen; Hu, Yixin; Wang, Fangfang; Zhang, Jingzhu; An, Li
Abstract : GABA was shown to have an antagonistic effect on AD by regulating CNTN1/2. Furthermore, circAPLP2 was found to be down-regulated in the AD brain, and the CEBPα/circAPLP2/miR-671-5p pathway mediates the regulation of CNTN1/2 expression by GABA. Abstract : The expression levels of the synaptic-related proteins contactin 1/2 (CNTN1/2) are down-regulated in the brain of Alzheimer's disease (AD), but the mechanism has not been clarified. γ-Aminobutyric acid (GABA) is considered a biologically active ingredient in food. Our previous research revealed that GABA can regulate CEBPα expression in Aβ-treated U251 cells. However, it is uncertain whether GABA can antagonize the pathogenesis of AD. Whether GABA can inhibit the reduction in CNTN1/2 expression by regulating CEBPα/circAPLP2/miR-671-5p in the AD brain remains unclear yet. Here, we demonstrate that GABA could attenuate the deposition of Aβ in the brain and ameliorate cognitive impairments in AD model mice. The expressions of CEBPα, circAPLP2, and CNTN1/2 were decreased and that of miR-671-5p was increased in AD model mouse brains and Aβ-induced SH-SY5Y cells. These alterations were partly reversed by GABA. The CNTN1/2 expression was down-regulated and up-regulated in SH-SY5Y cells treated with miR-671-5p mimics and miR-671-5p inhibitors, respectively. The results from the luciferase reporter assay revealed that miR-671-5p could bind to the 3′-untranslated region of circAPLP2. The silencing of circAPLP2 with the siRNA duplex caused an up-regulation of miR-671-5p and a down-regulation of CNTN1/2 in SH-SY5Y cells. The silencing of CEBPα with the siRNA duplex caused a down-regulation of circAPLP2 or CNTN1/2 and an up-regulation of miR-671-5p. In conclusion, GABA may decrease the deposition of Aβ in the brain, inhibit the down-regulation of CNTN1/2 expression, and ameliorate the cognitive deficits of AD model mice. The CEBPα/circAPLP2/miR-671-5p pathway plays a role in regulating CNTN1/2 expression by GABA in AD.